1995
DOI: 10.1149/1.2048677
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Studies of the Use of an Automated Flow‐Cell Electrodeposition System for the Formation of CdTe Thin Films by Electrochemical Atomic Layer Epitaxy

Abstract: This paper is the first report of the formation of thin films, thicker than ten monolayers, using electrochemical atomic layer epitaxy (ECALE). Thin films of CdTe have been electrodeposited on polycrystalline gold substrates in an electrochemical thin-layer flow-cell deposition system using the ECALE methodology. Studies of the deposit morphology have been performed using scanning electron microscopy and atomic force microscope. Significant improvements in deposit morphology are reported as a result of changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 3 publications
1
42
0
Order By: Relevance
“…This technique also allows for the decomposition of the deposition process into a series of individual steps with each step being independently optimized. Huang and co-workers [67] showed that thick films of CdTe (beyond 10 monolayers) can be deposited with this technique; however, they stated that film morphology suffers above 100 cycles. This technology relies on a thorough understanding of the fundamental mechanisms for the deposition of the constituent elements in atomic monolayers, and this was investigated by this group [68][69][70] and useful experimental data are provided in these references.…”
Section: Cadmium Telluride (Cdte)mentioning
confidence: 99%
“…This technique also allows for the decomposition of the deposition process into a series of individual steps with each step being independently optimized. Huang and co-workers [67] showed that thick films of CdTe (beyond 10 monolayers) can be deposited with this technique; however, they stated that film morphology suffers above 100 cycles. This technology relies on a thorough understanding of the fundamental mechanisms for the deposition of the constituent elements in atomic monolayers, and this was investigated by this group [68][69][70] and useful experimental data are provided in these references.…”
Section: Cadmium Telluride (Cdte)mentioning
confidence: 99%
“…In Table 1 we report the different thin films considered in this study. All syntheses were carried out by means of an automated deposition system, consisting of a distribution system composed of Pyrex bottles, electrochemical cells, a potentiostat, a control system for the solenoid valves and the stability of the potential [18,19]. This automated system allows a combination of the solutions within the electrochemical cell ensuring good fluid dynamics and a low contamination due to exposure to air.…”
Section: Methodsmentioning
confidence: 99%
“…If the sequence in Figure 3.2 is repeated an arbitrary number of times, a multilayer structure consisting of homo-or heteroepitaxial monoatomic layers is obtained [21]. Film growth using this protocol can be automated with an experimental apparatus for electrochemical atomic layer epitaxy (ECALE) developed by Stickney et al [51]. An additional variation of the SLRR protocol for thin film growth applications was reported recently [17].…”
Section: General Descriptionmentioning
confidence: 99%